Optically transparent melamine-formaldehyde polymers modified with proton acceptors - Lebedev, V. V.; Blank, T. A.; Avramenko, V. L.; Eksperiandova, L. P.; Mishurov, D. A.; Titskaya, V. D.; Shadrikov, A. S. (Institute for Single Crystals, 2009)
Investigation of reaction water binding in melamine-formaldehyde polymers with proton accepting compounds has shown that the use of dymethil sulfoxide in 1/1 (v/v) ratio provides preparation of optically transparent materials. Introduction of dymethil formamide and dymethil sulfoxide improves the main characteristics of the material, but modification with dymethil formamide reduces the polymer transparency.

Дослідження процесів зв'язування реакційної води у меламіно-формальдегідних полімерах за допомогою протоноакцепторних сполук показало, що при застосуванні диметилсульфоксиду в об'ємному співвідношенні 1:1 можна одержати оптично прозорі матеріали. Введення диметилформаміду та диметилсульфоксиду покращує основні характеристики матеріалу, однак модифікація диметилформамідом знижує прозорість полімерів.
Оптично прозорі меламіно-формальдегідні полімери, що модифіковані протоноакцепторними сполуками